EFFECTS OF SELF-ASSESSMENT IN EDUCATION - Elov Farrukh Akmalovich (Ustozlar uchun, 2025)
Self-assessment is an educational practice where students evaluate their own learning progress, performance, and understanding. This article explores the effects of self-assessment in education, focusing on its impact on student motivation, academic performance, metacognitive skills, and engagement. Drawing on empirical studies, the article analyzes the benefits, challenges, and best practices of implementing self-assessment in various educational contexts. It also examines how self-assessment fosters learner autonomy and critical thinking while addressing potential limitations such as subjectivity and lack of training. The article provides insights into how educators can effectively integrate self-assessment into teaching practices to enhance learning outcomes. Intended for educators, researchers, and policymakers, this article offers a comprehensive overview of self-assessment’s role in modern education and suggests directions for future research.